STUDI KELAYAKAN BISNIS ES TEH CUP: ANALISIS PELUANG USAHA DI ERA DIGITAL : STUDI KASUS PADA “ES TEH KITA” - Asri Utami; Lisa Permatasari; Dwi Astuti (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
The business feasibility study of “Iced Tea Cup” in the digital era shows significant potential for this beverage business, especially in the Jabodetabek area. With the growth of the Ready-to-Drink (RTD) beverage industry reaching 8.5% by 2022 and the high demand for practical products, this business has a great opportunity. Market analysis shows a target demographic of 15-35 years old, with a focus on consumers who prioritize practicality and affordable prices. “Es Teh Kita” is strategically located in Cikarang and offers products with affordable prices and distinctive flavors. Although it faces challenges such as high competition and limited capital for digital expansion, the opportunity to utilize online platforms and social media is huge. SWOT analysis shows strengths in products and location, but also weaknesses in operational management and dependence on weather. With positive revenue projections and a payback period achieved in two months, the venture is considered viable. The proposed digital marketing strategy includes social media optimization, cooperation with food delivery platforms, and loyalty programs.